THE POSSIBILITIES OF COMPUTED TOMOGRAPHY IN DIAGNOSE OF THE STATE OF CORONARY ARTERIES IN PATIENTS WITH ISCHEMIC HEART DISEASE - V. A. Azizov; M. J. Sultanova; K. I. Uludag; L. G. Ephendieva (Евразийский Кардиологический Журнал, 2014)
This research was aimed to study the possibilities of multislice computed (MSCT) tomography to diagnose status of coronary arteries at the patients with ischemic heart diseases. Material and methods. The research includes the results of complex study of 70 patients, which were send to the cardiology department for the verification of ischemic heart disease, as well as for examination and correction of provided therapy at this category. All patients had been provided traditional invasive coronary angiography and MSCT of coronary arteries. Results. At the 29 (76,3%) patients of 1 group stenosis of coronary arteries were not revealed, in 6 (15,8%) patients were revealed insignificant hemodynamic stenosis. In 3 (7,9%) patients revealed significant hemodynamic stenosis and in 1 (2,6%) critical stenosis (narrowing coronary artery lumen КА > 90 %). By data of MSCT and coronary angiography was revealed strong correlative relationship in diagnosis of stenosis. These factors argue about high comparability of both methods. The greatest correlation relationship was revealed for trunk of left coronary artery, right descending artery and circumflex artery and was 9,2; 0,84 and 0,81 accordingly. Analogical indexes were less for the right coronary artery and was 0,71. Though, large part of the patients in main group was not needed in intracoronary intervention and surgical revascularization. Conclusion. MSCT can use as noninvasive alternative method of coronary angiography in patients with high risk of ischemic heart disease. Comparative analysis of MSCT of coronary arteries and invasive coronary angiography revealed that MSCT has sensitivity of 91%, specificity of 89%.